Evaluation of Relationships between Drilling Rate Index and Physical and Strength Properties of Selected Rock Units of Pakistan - Shafique, U.; Abu Bakar, M. Z. (The Nucleus, 2015)
Fifteen selected rock types collected from different formations of Pakistan were subjected to Drilling Rate Index (DRI) tests and various physical and strength properties tests including, porosity (n), density, primary wave velocity (Vp), uniaxial compressive strength (Ïƒc), Brazilian tensile strength (Ïƒt) and Schmidt hammer rebound number (Rn),. Prior knowledge of the drill ability of rocks and their physico-mechanical properties plays a decisive role in planning and design of rock drilling and excavation processes. DRI tests developed by NTNU/SINTEF are in use by the industry since 1960s and have proved very successful in estimation of the boreability of rocks, but no such work has been reported for Pakistani rocks to date. Reasonable correlations were found between the DRI and the properties of the tested rocks. The trends shown in this paper are of interest for the machine manufacturers and operators working on various projects involving the use of drilling machines and other mechanical excavators.